Numerical analysis for supporting and deformation of complex foundation pit groups in unstable areas of karst strata - Li, Bin; Lin, Zhaorui; Chen, Yonggang; Xu, Changjie; Li, Peng; Ding, Haibin (Frontiers in Earth Science, 2023)
Due to the extensive karst development zone in karst areas, the stability of the underground soil layer is poor. The support of foundation pits in this area will be affected by complex environmental factors, and if not handled properly, it will cause significant safety hazards and economic losses. In this paper, the three-dimensional finite element model of the complex foundation pit and adjacent foundation pit group was established with the help of Midas GTS NX numerical software, and numerical simulation was carried out for the whole foundation pit excavation and construction process, and the deformation results of the adjacent foundation pit support structure of the complex foundation pit group and the soil outside the foundation pit were obtained. The results show that the underground wall of the complex foundation pit shifted to the north under the action of buttresses, with a similar "cantilever" displacement pattern on the south side of the underground wall in the center, a "push-back displacement" on the north side of the underground wall in the center, and a "ventral" displacement pattern at the corners of the grounded wall and on the east and west sides. Combined with the field measurement data, the support piles in the internal support system have a "cantilever" displacement pattern under the condition of massive soil unloading in the vicinity of the foundation pit, while the supporting piles show a "parabolic" displacement pattern under the action of the corner internal support. The deformation characteristics of the foundation pit in the presence of adjacent pits are significantly different from the results based on empirical laws. The results of the above study will provide useful technical guidance for the safety of excavation support for foundation pit groups in complex environments and the reasonable control of the surrounding environment.